An 18-month-old girl with Vici syndrome: A case report study - Parsa Forouhar; Mohammad Amin Eghtedari; Maryam Taraz; Mahsa Abdullahpour; Mohammad Mehrpouyan; Zhale Askarzade (Molecular Genetics and Metabolism Reports)
We report an 18-month-old female diagnosed with Vici syndrome, a rare congenital disorder characterized by developmental delay, albinism, cataracts, agenesis of the corpus callosum, hypotonia, and immunological anomalies. The patient, the second child of healthy first-cousin parents, presented with hypotonia at birth and subsequently developed bilateral cataracts, feeding difficulties, and multiple systemic manifestations, including kidney, bladder, and gallstones, as well as cardiomegaly and seizures. Genetic testing identified homozygous mutations in the EPG5 gene, confirming the diagnosis of Vici syndrome. The cardiac evaluation revealed a unique finding: serial echocardiograms initially detected multiple masses, which later regressed spontaneously, suggestive of a cardiac rhabdomyoma.